2008
DOI: 10.3892/or.19.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor induces anoikis resistance by up-regulation of cyclooxygenase-2 expression in uterine endometrial cancer cells

Abstract: Cyclooxygenase-2 (COX-2) has been implicated in the promotion of carcinogenesis. Although the role of COX-2 in endometrial cancer remains unclear, recent experiments suggest that COX-2 antagonizes cell apoptosis, increases the invasiveness of malignant cells, and promotes angiogenesis. Hepatocyte growth factor (HGF) is a mesenchymal-derived cytokine and the interaction between HGF and its tyrosine kinase receptor, c-Met proto-oncogene, is associated with tumor progression and metastasis. To investigate the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…COX-2 and PGE 2 play important roles in breast cancer metastasis (Ma et al, 2006;Ho et al, 2013;Sun et al, 2013) and contribute to anoikis resistance in several cancer cell lines (Zeng et al, 2002;Choi et al, 2005;Kanayama et al, 2008;Yoshizawa et al, 2011). PGE 2 suppresses detachmentinduced apoptosis in rat intestinal epithelial cells, and prostaglandin receptor (EP) 4, one of the PGE 2 receptors, is related to delayed anoikis by PGE 2 (Joseph et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…COX-2 and PGE 2 play important roles in breast cancer metastasis (Ma et al, 2006;Ho et al, 2013;Sun et al, 2013) and contribute to anoikis resistance in several cancer cell lines (Zeng et al, 2002;Choi et al, 2005;Kanayama et al, 2008;Yoshizawa et al, 2011). PGE 2 suppresses detachmentinduced apoptosis in rat intestinal epithelial cells, and prostaglandin receptor (EP) 4, one of the PGE 2 receptors, is related to delayed anoikis by PGE 2 (Joseph et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, in uterine endometrial cancer cells, HGF induces anoikis resistance through a PI3K-Akt pathwaydependent up-regulation of cyclooxygenase-2 (COX-2) expression. Similarly, Met receptor induces anoikis resistance in head and neck squamous cell carcinoma cells by activation of ERK and PI3K/Akt signalling [104]. Moreover, recently it has been reported that breast cancer cells undergoing EMT acquire many of the properties of cancer stem cells [105,106].…”
Section: Taddei Et Almentioning
confidence: 99%
“…Tumor cells lacking anchorage could escape from anoikis by forming multicellular aggregates through FAK phosphorylation [39]. Also, Kanayama et al [40] reported that HGF induces anoikis resistance by up-regulation of cyclooxygenase-2 expression in uterine endometrial cancer cells. In contrast to their studies, we did not observe FAK phosphorylation in CT26 transfectants in suspension even after addition of HGF.…”
Section: Discussionmentioning
confidence: 97%